2020
DOI: 10.1145/3415231
|View full text |Cite
|
Sign up to set email alerts
|

How Experts Detect Phishing Scam Emails

Abstract: Phishing scam emails are emails that pretend to be something they are not in order to get the recipient of the email to undertake some action they normally would not. While technical protections against phishing reduce the number of phishing emails received, they are not perfect and phishing remains one of the largest sources of security risk in technology and communication systems. To better understand the cognitive process that end users can use to identify phishing messages, I interviewed 21 IT experts abou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 35 publications
2
26
0
Order By: Relevance
“…When judging the safety of a URL, experts generally have more experience and data sources to draw from but at the end they look for discrepancies in the data and their expectations [84]. They can collect the data using tools like WHOIS (ICANN's domain lookup) to learn about the registered domain owner or understand the implications of a links up-time and popularity.…”
Section: Take Down Policymentioning
confidence: 99%
See 1 more Smart Citation
“…When judging the safety of a URL, experts generally have more experience and data sources to draw from but at the end they look for discrepancies in the data and their expectations [84]. They can collect the data using tools like WHOIS (ICANN's domain lookup) to learn about the registered domain owner or understand the implications of a links up-time and popularity.…”
Section: Take Down Policymentioning
confidence: 99%
“…Humans are the last point of defense for organizations as detecting phishing emails requires humans awareness of the context in which they received the phishing message, such as who they expect to receive the message from and which website they expect to visit [84]. Experts, for example, identify phishing emails by hovering over links, looking at sender emails address, and other technical information of the email; they typically learn to look at these features from training materials [84]. Training average users to identify phishing messages is a common approach which is often combined with automatic detection [9,12,43,74].…”
Section: User Trainingmentioning
confidence: 99%
“…However, despite the ‘availability of myriads anti-phishing systems, phishing continues unabated due to inadequate detection of a zero-day attack, superfluous computational overhead and high false rates’ [ 30 , p.1]. Moreover, in their research, Wash [ 50 ] found that while technical protections against phishing reduce the number of phishing emails received, they are not perfect. This could be because individual’s phishing susceptibility may be shaped by recent phishing encounters and, more importantly, that the effect of new experience on susceptibility will be heterogeneous among users [ 9 , p.1].…”
Section: Introductionmentioning
confidence: 99%
“…This could be because individual’s phishing susceptibility may be shaped by recent phishing encounters and, more importantly, that the effect of new experience on susceptibility will be heterogeneous among users [ 9 , p.1]. To better understand the cognitive process that end users can use to identify phishing messages, Wash [ 50 ] interviewed number of IT experts about where they successfully identified emails as phishing in their own inboxes. The problem is ‘the variety of phishing attacks is very broad, and usage of novel, more sophisticated methods complicate its automated filtering’ [ 33 , p.1].…”
Section: Introductionmentioning
confidence: 99%
“…Yet, all phishing emails with links can be identified through the URL behind each link. However, [23] showed that most people are not aware of this and [3] demonstrated that people have problems reading URLs correctly.…”
Section: Introductionmentioning
confidence: 99%